The Mediating Role of Non-Performing Financing (NPF) in the Financial Performance of Islamic Commercial Banks in Indonesia - Muthmainnah, Muthmainnah; Tiara, Tiara; Kartini, Titin (International Journal of Islamic Business and Economics (IJIBEC), 2024)
This study explores the impact of mudharabah and ijarah financing on the financial performance of Islamic commercial banks in Indonesia, with Non-Performing Financing (NPF) as a mediating variable. It addresses the challenge of maintaining profitability while managing financing risks in Indonesia's Islamic banking sector. Using a quantitative approach, secondary data from 2021 to 2023 were analyzed, sourced from the Financial Services Authority (OJK) and financial reports of Islamic banks. Path analysis with IBM AMOS 22 was conducted to assess the direct and indirect effects of these financing types on Return on Assets (ROA). The results show that mudharabah financing does not significantly affect NPF or ROA, while ijarah financing has a significant negative impact on both. NPF plays a key role as a mediating variable, with a total indirect effect of 47.5% on profitability. However, the size of this effect requires further validation through alternative models. These findings contribute to Islamic banking literature by identifying NPF as a crucial link between financing risks and bank profitability. The study emphasizes the importance of managing ijarah and mudharabah contracts carefully to enhance the financial resilience and sustainability of Islamic banks, especially in the post-pandemic recovery phase.